Comfort Evaluation of Slow-Recovery Ejection Seat Cushions Based on Sitting Pressure Distribution - Bao, Jiayi; Zhou, Qianxiang; Wang, Xingwei; Yin, Chao (Frontiers in Bioengineering and Biotechnology, 2021)
Sitting discomfort not only affects the health of pilots carrying out long-endurance missions but also affects operational performance. The experimental objects included four ejection seat cushions: N1 was a fast-recovery foam as the comparison group, and the experimental groups were slow-recovery foams with different indentation force deflection (IFD), named N2 (hard), N3 (mid), and N4 (soft). The sitting comfort of twenty participants was tested on the four cushions by using subjective rating and sitting pressure distribution analysis. The results showed that compared with fast-recovery cushion, N3 and N4 slow-recovery cushions have lower contact pressure and more uniform pressure distribution. Slow-recovery cushions that were too soft or too hard would reduce the comfort. No matter from the subjective rating or the analysis of the contact pressure data, the N3 cushion with a thickness of 3cm, 65% IFD of 280N had the highest comfort. In addition, the seat pressure distribution (SPD%) has a significant correlation with the subjective rating (P = 0.019, R = -0.98)， which is more suitable for evaluating the comfort of the cushions. However, the slow-recovery cushions would show a decrease in support after a period of sitting, while the fast-recovery cushion could always maintain constant support.